Strategi Optimalisasi Peran BMT dalam Membangun Perekonomian Jawa Timur - Ujang Syahrul Mubarrok; Beny Mahyudi Saputra; Muhammad Akbar Izzulhaq (Universitas Muhammadiyah Ponorogo, 2022)
The positive economic development of East Java was also followed by the development of the Islamic business industry. Various areas in East Java have established Islamic industries, such as Islamic hotels, halal culinary arts, halal tourism, and Islamic banks as Islamic financial service industries. Islamic banks as financial institutions that provide financing to the public, in their operations have not fully reached the micro-business sector in the lower East Java community. Small and micro customers who do not have collateral are paid less attention. Therefore, microfinance institutions such as Baitul Maal wat Tamwil (BMT) are needed to provide financing for micro-customers for the lower community in East Java. BMT itself has a dual role as a social institution managing ZISWAF funds and managing commercial and customer deposits. However, in its journey, BMT experienced several problems such as human resources and public perception of BMT which was still negative. So it takes a strategy to optimize the role of BMT in building the economy. This study aims to formulate a strategy to optimize the role of BMT by using SOAR analysis (strength, opportunity, aspiration, and result). Some of the strategies obtained from the discussion of this research are improving the quality of management and operations, strengthening the business structure and infrastructure of BMT, improving the quality of sharia supervision and compliance, empowering the community, and improving the people's economy.